Antimicrobial activity of garcinia kola (Heckel) seed extracts and isolated constituents against caries-causing microorganisms (2014)
Garcinia kola Heckel (Guttiferae) seed, has found use in folkloric medicine of Southern Nigeria for the treatment of toothache and prevention of dental caries. The crude ethanolic extract, chromatographic fractions and isolated constituents of Garcinia kola seed against clinical strains of dental-caries-causing and related microorganisms is being evaluated. Antimicrobial evaluations were done by testing different concentrations of the crude extract, vacuum liquid chromatographic (VLC) fractions and pure isolates against Streptococcus mutans, Streptococcus viridans and Staphylococcus aureus in already set blood agar with gentamicin as the reference standard. The zones of inhibition and minimum inhibitory concentrations (MIC) were determined as appropriate. Fraction N, eluted with (hexane: ethyl acetate 70: 30), exhibited the highest activity with MIC’s of 1.50 mgml⁻¹ and 0.33 mgml⁻¹ while the pure isolates 1 (cycloartenol) and 2 (24-methylenecycloartanol) gave MIC’s of 0.17 mgml⁻¹ and 0.38 mgml⁻¹ against Streptococcus mutans and Streptococcus viridans respectively. Isolate 3 (garcinianin) gave MIC of 1.0 mgml⁻¹ against Streptococcus mutans but there was no significant activity against Streptococcus viridans and Staphylococcus aureus. The results provide justifications for the folkloric use of Garcinia kola Heckel (Guttiferae) for dental caries-related health problems while the isolated compounds may also serve as templates for future antimicrobial drug development.